Determinants of Interest and Behavior in Stock Investment (Study of Semarang University Students) - Evi, Evi (IJOSMAS, 2021)
The capital market investment is one of alternative investment which is easily accessed by the wider community. Unfortunately, the interest of Indonesian people to be invested was still quite low. There were some differences in the results of research on attitudes towards investment interests, thus forming benefits and ease of investment variables, and making attitude as an intervening variable. The purpose of this research was to be found out, analyzed , and obtained empirical evidence about the determinants of interest and behavior of stock investment in Semarang University students.These research was conducted on 175 people of Semarang University students, by using purposive sampling method. These analysis technique used Structural Equation Modeling (SEM) by using the SmartPLS tools.The results of this research indicate that the benefits and ease of investment have significant effects on attitude. The benefits of investment, attitude, environment have significant effects on the interest in investing. Investing interests affected with investment behavior . This research has an attitude and interested in investing variables as intervening variables. The ease of investment and pocket money does not have significant effects on investment interests. Pocket money did not have significant effects on investment behavior